Bilateral arm power imbalance in swim bench exercise to exhaustion - Potts, A. D.; Charlton, J. E.; Smith, H. M. (Journal of Sports Sciences, 2002)
We examined the supposition that swimmers may exhibit an imbalance in bilateral arm power output during simulated swimming exercise. Ten competitive front crawl swimmers (5 males, 5 females; age 20.5+/-2.3 years; height 1.74+/-0.09 m; body mass 72.0+/-16.7 kg; 400 m freestyle swim time 278+/-20.5 s; mean +/- s) performed four incremental (10 W x min(-1)) swim ramp tests on a computer-interfaced biokinetic swim bench ergometer. External power output from each arm was measured continuously to exhaustion. The results showed that, throughout the course of the simulated swim, external power output clearly favoured the left arm (F1,9 = 12.5, P= 0.006). This was especially evident in the final 30 s to exhaustion, when 54.0+/-3.87% of external power output was derived from the left arm versus 46.0+/-3.87% from the right arm. The disparity in external power output was further highlighted when the participants were grouped into unilateral and bilateral breathers. Unilateral breathers (n = 5) produced 57.1+/-2.62% of external power output from the left armversus 42.9+/-2.62% from the right arm (P= 0.001). Bilateral breathers (n = 5) exhibited a more balanced external power output of 51.0+/-1.82% from the left arm and 49.0+/-1.82% from the right arm (P = 0.177). Evidence of power imbalance in the simulated swimming stroke may have important implications for optimizing swim performance. The observed power imbalance may be reduced when a bilateral breathing technique is adopted.